2016
DOI: 10.1002/ajh.24581
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A mutations are associated with inferior overall and leukemia‐free survival in chronic myelomonocytic leukemia

Abstract: DNMT3A mutations are seen in~5% of patients with chronic myelomonocytic leukemia (CMML) and thus far, have had an indeterminate prognostic impact on survival. We carried out this study to assess the prognostic impact of DNMT3A mutations on a larger informative cohort of CMML patients (n 5 261). DNMT3A mutations were seen in 6% (n 5 16); 56% (n 5 9) male, with a median age of 64 years. Eighty-one % of DNMT3A mutations were missense, with the Arg882 mutational hot spot accounting for 63% of all changes. Five (31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 31 publications
(52 reference statements)
2
49
1
Order By: Relevance
“…In order to address concerns regarding confounding from inadvertent inclusion of patients with chronic myelomonocytic leukaemia (CMML), we recently employed a multiparametric flow cytometry‐based approach and demonstrated qualitative differences in monocytes between CMML and myeloproliferative neoplasm (MPN)‐associated monocytosis; the classic monocyte fraction (CD14‐positive and CD16‐negative) was <92% in all MPN cases versus ≥94% in 93% of CMML patients (Patnaik et al , ). Furthermore, in the current study, the driver mutational frequency was similarly high in the presence or absence of monocytosis, which strongly argues against significant contamination of our study population by cases with CMML; reported mutational frequencies for JAK2 , CALR and MPL in CMML were only 7%, 0·5% and 0·5%, respectively (Patnaik et al , ). The findings from the current study suggest that the AMC should be included in future prognostic models for PMF.…”
Section: Presenting Clinical and Laboratory Features Of 454 Patients supporting
confidence: 47%
“…In order to address concerns regarding confounding from inadvertent inclusion of patients with chronic myelomonocytic leukaemia (CMML), we recently employed a multiparametric flow cytometry‐based approach and demonstrated qualitative differences in monocytes between CMML and myeloproliferative neoplasm (MPN)‐associated monocytosis; the classic monocyte fraction (CD14‐positive and CD16‐negative) was <92% in all MPN cases versus ≥94% in 93% of CMML patients (Patnaik et al , ). Furthermore, in the current study, the driver mutational frequency was similarly high in the presence or absence of monocytosis, which strongly argues against significant contamination of our study population by cases with CMML; reported mutational frequencies for JAK2 , CALR and MPL in CMML were only 7%, 0·5% and 0·5%, respectively (Patnaik et al , ). The findings from the current study suggest that the AMC should be included in future prognostic models for PMF.…”
Section: Presenting Clinical and Laboratory Features Of 454 Patients supporting
confidence: 47%
“…6 A 29-gene panel targeted exome capture assay was carried out on BM DNA specimens obtained at CMML diagnosis in 85 (62%) patients, for the following genes; TET2, DNMT3A, IDH1, IDH2, ASXL1, EZH2, SUZ12, SRSF2, SF3B1, ZRSR2, U2AF1, PTPN11, Tp53, SH2B3, RUNX1, CBL, NRAS, KRAS, JAK2, CSF3R, FLT3, KIT, CALR, MPL, NPM1, CEBPA, IKZF, ETNK1 and SETBP1, by previously described methods. 5,16 Azacitidine and DAC were dosed according to the FDA approved dosing schedules, with dose adjustments carried out at physician discretion, based on response and tolerability. Responses to HMA therapy were assessed retrospectively using the 2006, IWG MDS response criteria and the 2015, IWG MDS/MPN overlap syndrome response criteria.…”
Section: Methodsmentioning
confidence: 99%
“…[8] NPM1 mutations are infrequent in CMML (<5%) and MDS (<5%) and have an unclear prognostic impact. [9-11] We carried out this study to assess the i) frequency and clinical correlates, ii) prognostic impact and iii) survival outcomes related to NPM1 mutations in CMML.…”
Section: To the Editormentioning
confidence: 99%
“…A 29 gene panel next generation sequencing assay was carried out on BM DNA specimens obtained at diagnosis for the following genes; TET2, DNMT3A, IDH1, IDH2 , ASXL1, EZH2, SUZ12 , SRSF2, SF3B1, ZRSR2, U2AF1 , PTPN11, Tp53, SH2B3, RUNX1, CBL, NRAS, KRAS, JAK2, CSF3R, FLT3, KIT, CALR, MPL , NPM1, CEBPA, IKZF,ETNK1 and SETBP1, by previously described methods. [5, 11] Statistical analyses considered parameters obtained at time of CMML diagnosis. Differences in the distribution of continuous variables between categories were analyzed by either Mann-Whitney or Kruskal-Wallis tests.…”
Section: To the Editormentioning
confidence: 99%